An analysis of code switching as a learning and teaching strategy in selected multilingual schools of Limpopo Povince - Senyatsi, Khensani Khutso (My University, 2012)
This study explored the use of code switching as a learning and teaching strategy among grade 11 mathematics literacy learners at selected high schools in Limpopo Province. This study, in exploring this use, discovered language problems faced by these learners in the mathematics literacy classroom. Language seemed to be the major barrier in the understanding of concepts in mathematics literacy; and the material being delivered to them. The study found out that the use of code switching, from English to mother tongue, in explaining some of the concepts greatly helped the learners understand their scope of work. The study recommends the use of code switching during mathematics literacy lessons to better facilitate the process of learning and teaching and to improve language performance of the learners
Thesis (M.A. (Linguistic Studies)) -- University of Limpopo, 2012
Keywords: Code switching; Language problems; Code switching (Linguistics); Multilingualism; Bilingualism; English language -- Social aspects -- South Africa -- Limpopo; Multilingual education